2019
DOI: 10.1097/md.0000000000017611
|View full text |Cite
|
Sign up to set email alerts
|

Can sural nerve injury be avoided in the sinus tarsi approach for calcaneal fracture?

Abstract: There is no consensus regarding the references to determine the exact location of the skin incision to minimize iatrogenic sural nerve injury in the sinus tarsi approach for calcaneal fracture.The purpose of this cadaveric study was to describe the anatomical course of the sural nerve in relation to easily identifiable landmarks during the sinus tarsi approach and to provide a more practical reference for surgeons to avoid sural nerve injury.Twenty-four foot and ankle specimens were dissected. The bony landmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
2
8
4
Order By: Relevance
“…12 Furthermore, the superior limb of the incision for the ELAC may put the SN at risk, as this incision begins approximately 6-8 cm above the skin of the heel at a point halfway between the posterior border of the fibula and the LBA and extends distally to meet its inferior limb, as illustrated in Figure 6. 12 Our mean horizontal distance from the SN to the DTLM was 1.7 ± 0.3 cm (n = 204; range, 0.8-3.0 cm), which is similar to the previously observed means of 1.5 cm (n = 24; range, 0.8-2.4 cm) by Park et al 28 and 1.4 cm (n = 20; range, 0.6-2.2 cm) by Eastwood et al 6 Our first quartile range for this measurement was 0.8-1.5 cm, which is also similar to the minimum values of 0.6 cm and 0.8 cm observed by Park et al 28 and Eastwood et al, 6 respectively. This may suggest a posterior boundary “safe zone” for the STA that extends no more than 0.8 cm posterior to the DTLM to avoid injury to the SN, which is similar to the posterior boundary of 0.6 cm suggested by Eastwood et al 6 Our proposed posterior boundary, shown in Figure 7, would result in an incision path that crossed over the SN in less than 1% of the MRI studies we analyzed (based on mean – 3 SD for this measurement).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…12 Furthermore, the superior limb of the incision for the ELAC may put the SN at risk, as this incision begins approximately 6-8 cm above the skin of the heel at a point halfway between the posterior border of the fibula and the LBA and extends distally to meet its inferior limb, as illustrated in Figure 6. 12 Our mean horizontal distance from the SN to the DTLM was 1.7 ± 0.3 cm (n = 204; range, 0.8-3.0 cm), which is similar to the previously observed means of 1.5 cm (n = 24; range, 0.8-2.4 cm) by Park et al 28 and 1.4 cm (n = 20; range, 0.6-2.2 cm) by Eastwood et al 6 Our first quartile range for this measurement was 0.8-1.5 cm, which is also similar to the minimum values of 0.6 cm and 0.8 cm observed by Park et al 28 and Eastwood et al, 6 respectively. This may suggest a posterior boundary “safe zone” for the STA that extends no more than 0.8 cm posterior to the DTLM to avoid injury to the SN, which is similar to the posterior boundary of 0.6 cm suggested by Eastwood et al 6 Our proposed posterior boundary, shown in Figure 7, would result in an incision path that crossed over the SN in less than 1% of the MRI studies we analyzed (based on mean – 3 SD for this measurement).…”
Section: Discussionsupporting
confidence: 89%
“…Our observed mean of 2.2 ± 0.4 cm for this measurement was notably greater than that observed by the majority of previous cadaveric studies, as demonstrated in Table 2. More importantly, however, our upper range of values, demonstrated by a fourth quartile range of 2.5-3.6 cm, was notably larger than the previously recorded maximums of studies by Lawrence et al, 20 Mestdagh et al, 25 and Park et al, 28 which recorded values of 2.1 cm, 2.5 cm, and 2.6 cm, respectively. This highlights the potential increased risk of iatrogenic injury to the SN when using inferior incisions during ankle surgery, such as those seen with the inferior limb of the ELAC, demonstrated in Figure 6.…”
Section: Discussioncontrasting
confidence: 76%
“…Therefore, this study further describes the relevant anatomy at the dorsolateral foot, which may be relevant in surgical planning to avoid iatrogenic injury to the LDCN. 30 24 -63 Eastwood et al, 1992 9 20 -24…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we first extended the skin incision anteriorly, reaching the calcaneocuboid joint in order to expose the anterolateral fragment. In an effort to keep the anteriorly extended incision from interacting with the course of the sural nerve, a skin incision was made horizontally parallel to the sole rather than toward the 4th metatarsal base [ 16 ]. After the exposure of the calcaneocuboid joint, we separated the anterolateral fragment from the surrounding soft tissue and retracted it anterosuperiorly as a bony flap, which we called an anterolateral fragment open-door technique ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…An approximate 7 cm skin incision was made horizontally from the distal tip of the fibula to the level distal to the calcaneocuboid joint. Such a horizontal, anteriorly extended incision makes it feasible to see the wide range of the subtalar joint from the calcaneocuboid joint to the posterior facet of the calcaneus, simultaneously avoiding the risk of iatrogenic sural-nerve injury [ 16 ]. A deep dissection was continued until the peroneal tendons were identified, retracted inferiorly, and kept within the tendon sheath.…”
Section: Methodsmentioning
confidence: 99%